Finding the Petroclival Carotid Artery: The Vidian–Eustachian Junction as a Reliable Landmark - Oakley, Gretchen M.; Ebenezer, Jareen; Hamizan, Aneeza; Sacks, Peta-Lee; Rom, Darren; Sacks, Raymond; Winder, Mark; Davidson, Andrew; Teo, Charles; Solares, C. Arturo; Harvey, Richard J. (Journal of Neurological Surgery Part B: Skull Base, 2018)
Introduction Identifying the internal carotid artery (ICA) when managing petroclival and infratemporal fossa pathology is essential for the skull base surgeon. The vidian nerve and eustachian tube (ET) cartilage come together at the foramen lacerum, the vidian–eustachian junction (VEJ). The ICA position, relative to the VEJ is described.Methods Endoscopic dissection of adult fresh-frozen cadaver ICAs and a case series of patients with petroclival pathology were performed. The relationship of the VEJ to the ICA horizontal segment, vertical segment, and second genu was assessed. The distance of the ICA second genu to VEJ was determined in coronal, axial, and sagittal planes. The length of the vidian nerve and ET was measured from the pterygopalatine fossa (PPF) and nasopharyngeal orifice to the VEJ.Results In this study, 10 cadaver dissections (82.3 ± 6.7 years, 40% female) were performed. The horizontal petrous ICA was at or behind VEJ in 100%, above VEJ in 100%, and lateral to VEJ in 80%. The vertical paraclival segment was at or behind VEJ in 100%, above in 100%, and medial in 100%. The second genu was at or behind VEJ in 100% (3.3 ± 2.4 mm), at or above in 100% (2.5 ± 1.6 mm), and medial in 100% (3.4 ± 2.0 mm). The VEJ was successfully used to locate the ICA in nine consecutive patients (53.3 ± 13.6 years, 55.6% female) where pathology was also present. The VEJ was 15.0 ± 6.0 mm from the ET and 17.4 ± 4.1 mm from the PPF.Conclusion The VEJ is an excellent landmark as it defines both superior and posterior limits when isolating the ICA in skull base surgery.
Keywords: endoscopic surgery; skull base; internal carotid artery; anatomy; vidian nerve; eustachian tube